PETROGENESIS OF PICRITIC MARE MAGMAS: CONSTRAINTS ON THE EXTENT OF EARLY LUNAR DIFFERENTIATION - Longhi J. (My University, 2006)
Calculations of isobaric batch, polybaric batch, and polybaric fractional melting have been carried out on a variety of proposed lunar and terrestrial source region compositions. Results show that magmas with a generally tholeiitic character-plagioclase and high-Ca pyroxene crystallize before low-Ca pyroxene reflecting relatively high Al2O3 concentrations (>12 wt%)-are the inevitable consequence of anhydrous partial melting of source regions composed primarily of olivine and two pyroxenes with an aluminous phase on the solidus. Low-Al2O3 magmas (<10 wt%), as typified by the green picritic glasses in lunar maria require deep (700-1000 km), low-al2O3 source regions without an aluminous phase. The difference between primitive and depleted mantle beneath mid-ocean ridges amounts to less than 0.1 wt% Al2O3, whereas formation of the green glass source region requires a net loss of between 1.5 and 2.5 wt% Al2O3. Basalt extraction cannot account for fractionations of this magnitude. Accumulation of olivine and pyroxene at the base of a crystallizing magma ocean is, however, an effective method for producing the necessary Al2O3 depletions. Both olivine-rich and pyroxene-rich source regions can produce the picritic magmas, but mixing calculations show that both types of source region are likely to be hybrids consisting of an early- to intermediate-stage cumulate (olivine plus enstatite) and a later stage cumulate assemblage. Mass balance calculations show that refractory element-enriched bulk Moon compositions contain too much Al2O3 to allow for the deep low-Al2O3 source regions even after extraction of an Al2O3-rich (26-30 wt%) crust between 50 and 70 km thick. © 2006 Elsevier Inc. All rights reserved.